A Molecular View of the Ionic Liquid Catalyst Interface of SCILLs: Coverage-Dependent Adsorption Motifs of [C4C1Pyr][NTf2] on Pd Single Crystals and Nanoparticles - Schuschke, Christian; Fromm, Lukas; Träg, Johannes; Stumm, Corinna; Hohner, Chantal; Eschenbacher, Roman; Grau, Sebastian; Zahn, Dirk; Görling, Andreas; Bauer, Tanja; Libuda, Jörg (Journal of Physical Chemistry C, 2021)
Solid catalysts with ionic liquid layers (SCILLs) are heterogeneous catalysts coated with a thin layer of an ionic liquid (IL) to improve their selectivity. In this study, we investigated the interplay of the roomerature IL 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide [C4C1Pyr][NTf2] with transition metal surfaces of both Pd(111) single crystals and Pd nanoparticles (NPs) supported on highly oriented pyrolytic graphite (HOPG). To this end, we combine theoretical insights obtained by density functional theory (DFT) and molecular dynamics (MD) calculations with experimental data acquired via time-resolved infrared reflection absorption spectroscopy (TR-IRAS) performed under ultrahigh vacuum (UHV) conditions. IL monolayer films formed on Pd(111) and Pd NPs are strongly bound to the surface via the SO2 moiety of the [NTf2]- anion. By combination of IRAS, DFT, and MD, we identify the most common adsorption motifs. Most importantly, the binding motif of the anion changes as a function of the IL coverage. On supported Pd NPs, additional effects arise from the particle morphology and from the diffusion of carbon from the support to the Pd NPs. Our results suggest that the effect of the IL film on the catalytic activity should strongly depend on the local coverage and the morphology of the catalyst NPs.
CRIS-Team Scopus Importer:2021-07-09

Atomic Layer Deposition on Spray-Dried Supraparticles to Rationally Design Catalysts with Ultralow Noble Metal Loadings - Groppe, Philipp; Müller, Valentin; Will, Johannes; Zhou, Xin; Zhang, Kailun; Moritz, Michael; Papp, Christian; Libuda, Jörg; Retzer, Tanja; Spiecker, Erdmann; Bachmann, Julien; Mandel, Karl; et al. (Chemistry of Materials, 2025)
The controlled assembly of supraparticles by using spray-drying enables the synthesis of nanoporous materials. Changing the size of the constituent nanoparticles or their agglomeration states provides access to a diverse range of pore frameworks. This turns supraparticles into ideal scaffolds in heterogeneous catalysis. The combination of supraparticles with atomic layer deposition (ALD) as a surface functionalization technique offers excellent control over the deposition of a functional material and its distribution over the scaffold on the nanoscale. This work reports the combination of SiO2 supraparticles as tunable scaffolds and their loading with a platinum-based ALD catalyst. The deliberate adjustment of the scaffold pore framework via spray-drying and its effect on the catalyst deposition are highlighted. Furthermore, varying numbers of Pt ALD cycles are applied to explore the capability of the combination approach with respect to catalyst loading and Pt efficiency. High-resolution electron microscopy reveals ultrasmall Pt clusters deposited on the supraparticles after the very first ALD cycle. Using the hydrogenation of 4-nitrophenol as a demonstration, the impact of the pore framework and the Pt deposition variation in ALD on the catalytic functionality is investigated.
Created from Fastlane, Scopus look-up

Boosting the activity of hydrogen release from liquid organic hydrogen carrier systems by sulfur-additives to Pt on alumina catalysts - Auer, Franziska; Blaumeiser, Dominik; Bauer, Tanja; Bösmann, Andreas; Szesni, Normen; Libuda, Jörg; Wasserscheid, Peter (Catalysis: Science and Technology, 2019)
Liquid organic hydrogen carrier (LOHC) systems are a promising alternative for energy storage and transport. The development of an active and selective LOHC-dehydrogenation catalyst is therefore of great importance. In this study we present a modification procedure of Pt/Al2O3 catalysts with a sulfur containing compound that results in improved activity as well as in reduced side product formation. Here, it appears that the right amount of applied sulfur species is crucial to reach the described effects. The optimum value depends on the support surface area and the molar ratio of sulfur to surface platinum. Mechanistic studies of the sulfur modification by infrared spectroscopy (DRIFTS) with adsorbed CO revealed that preferentially low coordinated defect sites (edges or corner/apex Pt atoms) are blocked by sulfur compounds and that these are the ones responsible for side reactions. The sulfur species were found to modify the electronic properties of Pt and this facilitates the desorption of the aromatic dehydrogenation products.
CRIS-Team Scopus Importer:2019-07-16

Catalyst Supraparticles: Tuning the Structure of Spray-Dried Pt/SiO2 Supraparticles via Salt-Based Colloidal Manipulation to Control their Catalytic Performance - Groppe, Philipp; Reichstein, Jakob; Carl, Simon; Cuadrado Collados, Carlos; Niebuur, Bart Jan; Zhang, Kailun; Apeleo Zubiri, Benjamin; Libuda, Jörg; Kraus, Tobias; Retzer, Tanja; Thommes, Matthias; Spiecker, Erdmann; et al. (Small, 2024)
The structure of supraparticles (SPs) is a key parameter for achieving advanced functionalities arising from the combination of different nanoparticle (NP) types in one hierarchical entity. However, whenever a droplet-assisted forced assembly approach is used, e.g., spray-drying, the achievable structure is limited by the inherent drying phenomena of the method. In particular, mixed NP dispersions of differently sized colloids are heavily affected by segregation during the assembly. Herein, the influence of the colloidal arrangement of Pt and SiO2 NPs within a single supraparticulate entity is investigated. A salt-based electrostatic manipulation approach of the utilized NPs is proposed to customize the structure of spray-dried Pt/SiO2 SPs. By this, size-dependent separation phenomena of NPs during solvent evaporation, that limit the catalytic performance in the reduction of 4-nitrophenol, are overcome by achieving even Pt NP distribution. Additionally, the textural properties (pore size and distribution) of the SiO2 pore framework are altered to improve the mass transfer within the material leading to increased catalytic activity. The suggested strategy demonstrates a powerful, material-independent, and universally applicable approach to deliberately customize the structure and functionality of multi-component SP systems. This opens up new ways of colloidal material combinations and structural designs in droplet-assisted forced assembly approaches like spray-drying.
CRIS-Team Scopus Importer:2024-05-10
Keywords: catalysis; porosity; spray-drying; structure control; supraparticles

CO Permeability and Wetting Behavior of Ionic Liquids on Pt(111): An IRAS and PM-IRAS Study from Ultrahigh Vacuum to Ambient Pressure - Blaumeiser, Dominik; Schuschke, Christian; Fromm, Lukas; Taccardi, Nicola; Schötz, Simon; Eschenbacher, Roman; Bühlmeyer, Hanna; Xu, Tao; Bauer, Tanja; Wasserscheid, Peter; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry C, 2021)
Solid catalysts with ionic liquid layers (SCILLs) show improved performance as compared to ionic liquid (IL)-free catalysts. To realize the beneficial IL-induced modification, the IL layer should be stable under reaction conditions but also permeable for gaseous reactants entering through the IL phase. Herein, we applied (polarization modulation-) infrared reflection absorption spectroscopy ((PM-)IRAS) to investigate the CO permeability of model SCILL systems. We investigated three different IL model systems prepared by physical vapor deposition (PVD) in ultrahigh vacuum (UHV) on atomically clean Pt(111), namely, 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide ([C4C1Pyr][NTf2]), 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2C1Im][NTf2]), and 1-butyl-1-methylpyrrolidinium trifluoromethanesulfonate ([C4C1Pyr][OTf]). The adsorption geometries of the anions depend on the surface structure, IL coverage, and precoverage of CO. At room temperature, IL multilayers of randomly oriented species grow on top of strongly adsorbed wetting layers. Upon heating, a partial wetting transition induces the coexistence of an IL wetting monolayer film with three-dimensional droplets. Gas-phase CO does not permeate through IL multilayers, while it penetrates the IL wetting monolayer leading to mixed IL/CO films. The partial dewetting transition and the permeability differ drastically with the temperature and IL. Consequently, the morphology of the IL films could be a factor that determines the catalytic behavior of SCILLs to a significant extent.
CRIS-Team Scopus Importer:2021-08-06

Cu carbonyls enhance the performance of Ru-based SILP water-gas shift catalysts: a combined in situ DRIFTS and DFT study - Blaumeiser, Dominik; Stepic, Robert; Wolf, Patrick; Wick, Christian; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Suncana; Bauer, Tanja; Libuda, Jörg (Catalysis: Science and Technology, 2020)
Ru-based supported ionic liquid phase (SILP) catalysts efficiently promote the water-gas shift reaction (WGSR). The addition of CuCl further improves the performance. This is attributed to the formation of labile Cu carbonyl species, which act as CO shuttles in the ionic liquid (IL) phase. We apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) to monitor the formation of these Cu carbonyls in an imidazolium-based SILP system. To aid the identification of the relevant Cu carbonyls, we perform density functional theory (DFT) calculations. In the present study, we investigate [Ru(CO)(3)Cl-2](2)/CuCl/[C(4)C(1)C(1)Im]Cl/Al2O3 and CuCl/[C(4)C(1)C(1)Im]Cl/Al2O3 with various CuCl : IL ratios. The relevant Cu carbonyls are identified as neutral CuCl monomers and dimers, as well as monoanionic monomers and dimers. Moreover, we demonstrate that the ratio of the individual Cu carbonyl species depends on the CuCl : IL ratio.
CRIS-Team WoS Importer:2020-01-17

Dynamic equilibria in supported ionic liquid phase (SILP) catalysis: in situ IR spectroscopy identifies [Ru(CO)xCly]n species in water gas shift catalysis - Bauer, Tanja; Stepic, Robert; Wolf, Patrick; Kollhoff, Fabian; Karawacka, Weronica; Wick, Christian; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Suncana; Libuda, Jörg (Catalysis: Science and Technology, 2018)
Ru-based supported ionic liquid phase (SILP) systems efficiently catalyze the low-temperature water-gas shift reaction (WGSR). While previous studies suggest that Ru-carbonyl species play an important role in the mechanism, detailed knowledge on the catalytically active species is still missing. To identify these carbonyl complexes, we apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT). Investigations of an as-prepared [R(CO)3Cl2]2/ [C4C1C1Im]Cl/Al2O3 catalyst indicate splitting of the dimer induced by Cl−. Subsequently, an equilibrium between several [R(CO)xCly]n species is established, in which the IL serves as an effectively infinite Cl− reservoir. We find that the major species in the system freshly-prepared from [R(CO)3Cl2]2 is indeed [R(CO)3Cl3]−. A smaller amount of [R(CO)2Cl3]− and chloride-rich species [R(CO)2Cl4]2− or [RuCOCl4]2− are also found in the SILP. Similar Ru-carbonyl species are observed during carbonylation of RuCl3/ [C4C1C1Im]Cl/Al2O3, another potential WGSR catalyst. The response of [Ru(CO)3Cl2]2/[C4C1C1Im]Cl/Al2O3 to heating and/or CO dosing was probed in situ and the results confirm the presence of the equilibrium proposed above.
Keywords: SILP catalysis; in situ IR spectroscopy; [Ru(CO)xCly]n species

Enhancing the feasibility of Pd/C-catalyzed formic acid decomposition for hydrogen generation - catalyst pretreatment, deactivation, and regeneration - Kosider, Axel; Blaumeiser, Dominik; Schötz, Simon; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter; Libuda, Jörg; Bauer, Tanja (Catalysis: Science and Technology, 2021)
Formic acid decomposition (FAD) generates H-2 at low temperatures. However, many known catalyst systems suffer from deactivation due to competing side reactions during FAD. In this work, we focus on the origins of the deactivation of Pd catalysts but also on protocols which allow for reactivation of this precious metal catalyst. We combined batch experiments with results from in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). We find that CO adsorbates block catalytic sites and deactivate the Pd catalyst. Oxidative treatment lifts this inhibition. Additionally, our results show that oxidative pretreatment activates the Pd catalyst, whereas reduction leads to a catalyst which is essentially inactive for FAD.
CRIS-Team WoS Importer:2021-05-28

Gluing Ionic Liquids to Oxide Surfaces: Chemical Anchoring of Functionalized Ionic Liquids by Vapor Deposition onto Cobalt(II) Oxide - Xu, Tao; Wähler, Tobias; Vecchietti, Julia; Bonivardi, Adrian; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Angewandte Chemie International Edition, 2017)
Ionic liquids (IL) hold a great potential as novel electrolytes for applications in electronic materials and energy technology. The functionality of ILs in these applications relies on their interface to semiconducting nanomaterials. Therefore, methods to control the chemistry and structure of this interface are the key to assemble new IL-based electronic and electrochemical materials. Here, we present a new method to prepare a chemically well-defined interface between an oxide and an IL film. An imidazolium-based IL, which is carrying an ester group, is deposited onto cobalt oxide surface by evaporation. The IL binds covalently to the surface by thermally activated cleavage of the ester group and formation of a bridging carboxylate. The anchoring reaction shows high structure sensitivity, which implies that the IL film can be adhered selectively to specific oxide surfaces.
Keywords: chemical anchoring; cobalt oxide; ester functionalization; ionic liquids; vapor deposition

Gluing ionic liquids to oxide surfaces: Chemical anchoring of functionalized ionic liquids by vapor deposition onto cobalt(II) oxide // Gluing Ionic Liquids to Oxide Surfaces: Chemical Anchoring of Functionalized Ionic Liquids by Vapor Deposition onto Cobalt(II) Oxide - Xu, Tao; Wähler, Tobias; Vecchietti, Ph. D. Maria Julia; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Angewandte Chemie, 2017)
Ionic liquids (IL) hold a great potential as novel electrolytes for applications in electronic materials and energy technology. The functionality of ILs in these applications relies on their interface to semiconducting nanomaterials. Therefore, methods to control the chemistry and structure of this interface are the key to assemble new IL-based electronic and electrochemical materials. Here, we present a new method to prepare a chemically well-defined interface between an oxide and an IL film. An imidazolium-based IL, which is carrying an ester group, is deposited onto cobalt oxide surface by evaporation. The IL binds covalently to the surface by thermally activated cleavage of the ester group and formation of a bridging carboxylate. The anchoring reaction shows high structure sensitivity, which implies that the IL film can be ``glued'' selectively specific oxide surfaces.
EAM Import::2019-03-13

Highly Effective Propane Dehydrogenation Using Ga-Rh Supported Catalytically Active Liquid Metal Solutions - Raman, Narayanan; Maisel, Sven; Grabau, Mathias; Taccardi, Nicola; Debuschewitz, Jonas; Wolf, Moritz; Wittkämper, Haiko; Bauer, Tanja; Wu, Mingjian; Haumann, Marco; Papp, Christian; Görling, Andreas; et al. (ACS Catalysis, 2019)
Our contribution demonstrates that rhodium, an element that has barely been reported as an active metal for selective dehydrogenation of alkanes becomes a very active, selective, and robust dehydrogenation catalyst when exposed to propane in the form of single atoms at the interface of a solid-supported, highly dynamic liquid Ga-Rh mixture. We demonstrate that the transition to a fully liquid supported alloy droplet at Ga/Rh ratios above 80, results in a drastic increase in catalyst activity with high propylene selectivity. The combining results from catalytic studies, X-ray photoelectron spectroscopy, IR-spectroscopy under reaction conditions, microscopy, and density-functional theory calculations, we obtained a comprehensive microscopy picture of the working principle of the Ga-Rh supported catalytically active liquid metal solution.
CRIS-Team Scopus Importer:2019-10-18
Keywords: alkane; alkene; catalysis; dehydrogenation; gallium; rhodium

Hydrogen Production Based on Liquid Organic Hydrogen Carriers through Sulfur Doped Platinum Catalysts Supported on TiO2 - Chen, Ximeng; Gierlich, Christian H.; Schötz, Simon; Blaumeiser, Dominik; Bauer, Tanja; Libuda, Jörg; Palkovits, Regina (ACS Sustainable Chemistry & Engineering, 2021)
In order to move from a carbon-based energy system to a more sustainable one, focus is put on liquid organic hydrogen carrier (LOHC) systems for CO2-free hydrogen storage and release. In this study sulfur as a dopant for the Pt/TiO2 catalyst was identified to be a selective poison resulting in high performing catalysts in the dehydrogenation experiments with the LOHC system perhydro dibenzyltoluene/dibenzyltoluene (H18-DBT/H0-DBT). The Pt/TiO2 and S-Pt/TiO2 catalysts were compared to the current benchmarks Pt/γ-Al2O3 and S-Pt/γ-Al2O3. S-Pt/TiO2 was found to achieve a high degree of dehydrogenation of 98% which is competitive to the benchmark S-Pt/γ-Al2O3. In addition, analyses of the side products resulted in a higher selectivity toward dibenzyltoluene for S-Pt/TiO2 than for the γ-Al2O3 supported catalysts. Characterization with infrared spectroscopy (IR), transmission electron microscopy (TEM), and diffuse reflectance infrared Fourier transform spectroscopy with CO as adsorbing molecule (CO-DRIFTS) suggest the presence of strongly chemisorbed sulfur species as well as SMSI effects of the Pt/TiO2 catalysts. Based on kinetic studies, a batch and plug flow reactor for the dehydrogenation reaction were simulated for both titania supported catalysts. According to the calculations, the sulfur doped catalyst displays higher conversions in both batch and plug flow operation as compared to the unmodified system Pt/TiO2.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Catalytic dehydrogenation; Dibenzyltoluene; Liquid organic hydrogen carrier; Perhydro dybenzyltoluene; Reversible hydrogen storage; Selective poisoning

Improving the Performance of Supported Ionic Liquid Phase Catalysts for the Ultra-Low-Temperature Water Gas Shift Reaction Using Organic Salt Additives - Wolf, Patrick; Wick, Christian; Mehler, Julian; Blaumeiser, Dominik; Schötz, Simon; Bauer, Tanja; Libuda, Jörg; Smith, David M.; Smith, Ana-Suncana; Haumann, Marco (ACS Catalysis, 2022)
The water gas shift reaction (WGSR) is catalyzed by supported ionic liquid phase (SILP) systems containing homogeneous Ru complexes dissolved in ionic liquids (ILs). These systems work at very low temperatures, that is, between 120 and 160 °C, as compared to >200 °C in the conventional process. To improve the performance of this ultra-low-temperature catalysis, we investigated the influence of various additives on the catalytic activity of these SILP systems. In particular, the application of methylene blue (MB) as an additive doubled the activity. Infrared spectroscopy measurements combined with density functional theory (DFT) calculations excluded a coordinative interaction of MB with the Ru complex. In contrast, state-of-the-art theoretical calculations elucidated the catalytic effect of the additives by non-covalent interactions. In particular, the additives can significantly lower the barrier of the rate-determining step of the reaction mechanism via formation of hydrogen bonds. The theoretical predictions, thereby, showed excellent agreement with the increase of experimental activity upon variation of the hydrogen bonding moieties in the additives investigated.
CRIS-Team Scopus Importer:2022-06-03
Keywords: electronic interaction; methylene blue; ruthenium; supported ionic liquid phase; water gas shift reaction

Improving the performance of supported ionic liquid phase (SILP) catalysts for the ultra-low-temperature water-gas shift reaction using metal salt additives - Wolf, Patrick; Aubermann, Manfred; Wolf, Moritz; Bauer, Tanja; Blaumeiser, Dominik; Stepic, Robert; Wick, Christian; Smith, David M.; Smith, Ana-Suncana; Wasserscheid, Peter; Libuda, Jörg; Haumann, Marco (Green Chemistry, 2019)
Supported ionic liquid phase (SILP) catalyst systems containing homogeneous Ru complexes dissolved in ionic liquids (ILs) catalyze the water-gas shift reaction (WGSR) at very low temperatures, i.e., between 120 and 160 °C. One limiting factor of the SILP WGS technology is the low solubility of CO in most ILs. To overcome this issue, we study the influence of different transition metal chloride additives on the activity of Ru-based WGS SILP catalysts. CuCl as the additive was found to enhance the activity by almost 30%. This increase in activity peaks at a CuCl addition of 4 M as a result of the interplay between the increasing CO uptake in the ionic liquid film as evidenced by means of CO sorption and thermogravimetry, and the increasing, unfavorable ionic liquid acidity at too high CuCl concentrations. The respective chlorocuprate species were identified by means of in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT) calculations. We attribute the enhanced catalytic performance to cuprate ions that act as CO shuttles within the ionic liquid film.
CRIS-Team Scopus Importer:2019-09-27

Interaction between Ionic Liquids and a Pt(111) Surface Probed by Coadsorbed CO as a Test Molecule - Eschenbacher, Roman; Schuschke, Christian; Bühlmeyer, Hanna; Taccardi, Nicola; Wasserscheid, Peter; Bauer, Tanja; Xu, Tao; Libuda, Jörg (Journal of Physical Chemistry Letters, 2021)
We used temperature-programmed infrared reflection absorption spectroscopy (TP-IRAS) to study the desorption behavior of CO on Pt(111) coadsorbed with four kinds of ionic liquids (ILs), namely 1-butyl-1-methyl-pyrrolidinium-bis(trifluoromethylsulfonyl)imide ([C4C1Pyr][NTf2]), 1-ethyl-3-methyl-imidazolium-bis(trifluoromethylsulfonyl)imide ([C2C1Im][NTf2]), 1-butyl-1-methyl-pyrrolidinium-trifluoro-methanesulfonate ([C4C1Pyr][OTf]), and 1-butyl-1-methyl-pyrrolidinium-hexafluorophosphate ([C4C1Pyr][PF6]). We found that CO desorbs earlier from a Pt(111) surface with coadsorbed ILs than without. In addition, the CO desorption temperature varies between different types of coadsorbed ILs, which follows the order: [C4C1Pyr][PF6] (365 K) > [C4C1Pyr][NTf2] (362 K) > [C2C1Im][NTf2] (352 K) > [C4C1Pyr][OTf] (348 K). We ascribe the difference in CO desorption temperature to the different interaction strength between ILs and the Pt(111) surface. A stronger IL-Pt(111) interaction leads to a lower CO desorption temperature. We suggest that TP-IRAS experiments of CO coadsorbed with ILs can be a useful method to aid the characterization of the interaction strength between ILs and metal surfaces such as Pt(111).
CRIS-Team Scopus Importer:2021-11-05

Interaction of Ester-Functionalized Ionic Liquids with Atomically-Defined Cobalt Oxides Surfaces: Adsorption, Reaction and Thermal Stability - Xu, Tao; Wähler, Tobias; Vecchietti, Julia; Bonivardi, Adrian; Bauer, Tanja; Schwegler, Johannes; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (ChemPhysChem, 2017)
Hybrid materials consisting of ionic liquid (ILs) films on supported oxides hold a great potential for applications in electronic and energy materials. In this work, we have performed surface science model studies scrutinizing the interaction of ester-functionalized ILs with atomically defined Co3O4(111) and CoO(100) surfaces. Both supports are prepared under ultra-high vacuum (UHV) conditions in form of thin films on Ir(100) single crystals. Subsequently, thin films of three ILs, 3-butyl-1-methyl imidazolium bis(trifluoromethyl-sulfonyl) imide ([BMIM][NTf2]), 3-(4-methoxyl-4-oxobutyl)-1-methylimidazolium bis(trifluoromethyl-sulfonyl) imide ([MBMIM][NTf2]), and 3-(4-isopropoxy-4-oxobutyl)-1-methylimidazolium bis(trifluoromethyl-sulfonyl) imide ([IPBMIM][NTf2]), were deposited on these surfaces by physical vapor deposition (PVD). Time-resolved and temperature-programmed infrared reflection absorption spectroscopy (TR-IRAS, TP-IRAS) were applied to monitor insitu the adsorption, film growth, and thermally induced desorption. By TP-IRAS, we determined the multilayer desorption temperature of [BMIM][NTf2] (360 +/- 5K), [MBMIM][NTf2] (380K) and [IPBMIM][NTf2] (380K). Upon deposition below the multilayer desorption temperature, all three ILs physisorb on both cobalt oxide surfaces. However, strong orientation effects are observed in the first monolayer, where the [NTf2](-) ion interacts with the surface through the SO2 groups and the CF3 groups point towards the vacuum. For the two functionalized ILs, the [MBMIM](+) and [IPBMIM](+) interact with the surface Co2+ ions of both surfaces via the CO group of their ester function. A very different behavior is found, if the ILs are deposited above the multilayer desorption temperature (400K). While for [BMIM][NTf2] and [MBMIM][NTf2] a molecularly adsorbed monolayer film is formed, [IPBMIM][NTf2] undergoes a chemical transformation on the CoO(100) surface. Here, the ester group is cleaved and the cation is chemically linked to the surface by formation of a surface carboxylate. The IL-derived species in the monolayer desorb at temperatures around 500 to 550K.
Keywords: chemical anchoring; cobalt oxide; ionic liquids; IRAS; thermal stability

Ionic Liquid-Modified Electrocatalysts: The Interaction of [C1C2Im][OTf] with Pt(1 1 1) and its Influence on Methanol Oxidation Studied by Electrochemical IR Spectroscopy - Brummel, Olaf; Faisal, Firas; Bauer, Tanja; Pohako-Esko, Kaija; Wasserscheid, Peter; Libuda, Jörg (Electrochimica Acta, 2016)
Ionic liquids (ILs) have recently been proposed as modifying agents to tune the selectivity and the activity of electrocatalysts. In order to explore the origin of IL-induced effects on electrocatalytic reactions, we have investigated (i) the interaction of [CCIm][OTf]-water mixtures with Pt(1 1 1) single crystal electrodes and (ii) the influence of [CCIm][OTf] on methanol oxidation in acidic aqueous solution using cyclic voltammetry (CV) and electrochemical IR spectroscopy. We show that [CCIm][OTf] interacts strongly with the Pt(1 1 1) surface in the potential range from -0.2 V to 0.65 V, leading to partial blocking of the surface, partial suppression of hydrogen adsorption, and partial suppression of OH formation. The interaction of the IL with Pt occurs in this potential range via specific adsorption of the [OTf] anions which bind to Pt(1 1 1) via the SO group in a tilted adsorption geometry. The adsorption process is largely reversible as a function of the electrode potential, but shows a complex kinetics and becomes very slow at high IL coverage. Also, [CCIm][OTf] has a strong effect on the electro-oxidation of methanol in acidic solution. Adsorption of [OTf] leads to partial blocking of the indirect oxidation pathway to CO. The onset potential for CO oxidation is found to be shifted to more positive values indicating hindered access of HO to the electrode surface. CO and the [CCIm][OTf] form a mixed co-adsorption layer which is characterized by a strongly red-shifted CO stretching band. The effect is assigned to an IL-induced ligand effect in the mixed adsorbate layer and suggests that the direct modification of active centers by surface-bound IL species plays an important role in IL-modified electrocatalytic materials.
Keywords: carbon monoxide; electrochemical IR spectroscopy; Ionic liquids; methanol oxidation; platinum

Ionic-Liquid-Modified Hybrid Materials Prepared by Physical Vapor Codeposition: Cobalt and Cobalt Oxide Nanoparticles in [C(1)C(2)Im][OTf] Monitored by In Situ IR Spectroscopy - Mehl, Sascha; Bauer, Tanja; Brummel, Olaf; Pohako-Esko, Kaija; Schulz, Peter; Wasserscheid, Peter; Libuda, Jörg (Langmuir, 2016)
The synthesis of ionic-liquid-modified nanomaterials has, attracted much attention recently. In this study we explore the potential to prepare such systems in an ultraclean fashion by physical vapor codeposition (PVCD). We codeposit metallic cobalt and the room-temperature ionic liquid (IL) 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [C(1)C(2)Im][OTf] simultaneously onto a Pd(111) surface at 100 K. This process is performed under ultrahigh-vacuum (UHV) conditions in the presence of CO, or in the presence of O-2 and CO. We use time-resolved (TR) and temperature-programmed (TP) infrared reflection absorption spectroscopy (IRAS) to investigate the formation and stability of the IL-modified Co deposits in situ during the PVD-based synthesis. CO is used as a probe molecule to monitor the growth. After initial growth of flat Co films on Pd(111), multilayers of Co nanoparticles (NPs) are formed. Characteristic shifts and intensity changes are observed in the vibrational bands of both CO and the IL, which originate from the electric field at the IL/Co interface (Stark effect) and from specific adsorption of the [OTf](-) anion. These observations indicate that the Co aggregates are stabilized by mixed adsorbate shells consisting of CO and [OTf](-). The CO coverage on the Co particle decreases with increasing temperature, but some CO is preserved up to the desorption temperature of the IL (370 K). Further, the IL shell suppresses the oxidation of the Co NPs if oxygen is introduced in the PVCD process. Only chemisorbed oxygen is formed at oxygen partial pressures that swiftly lead to formation of Co3O4 in the absence of the IL (5 X 10(-6) mbar O-2). This chemisorbed oxygen is found to destabilize the CO ligand shell. The oxidation of Co is not suppressed if IL and Co are deposited sequentially under otherwise identical conditions. In this case we observe the formation of fully oxidized cobalt oxide particles.

Ligand Effects at Ionic Liquid-Modified Interfaces: Coadsorption of [C(2)C(1)lm][OTf] and CO on Pd(111) - Bauer, Tanja; Mehl, Sascha; Brummel, Olaf; Pohako-Esko, Kaija; Wasserscheid, Peter; Libuda, Jörg (Journal of Physical Chemistry C, 2016)
Thin films of ionic liquids (ILs) can be used to tune the activity and selectivity of heterogeneous catalysts and electrocatalysts (solid catalysts with IL layer, SCILL). In several cases it has been found that these IL layers have a strong beneficial effect on the selectivity. To explore the molecular origin of this phenomenon, we have performed a model study on ultrahigh-vacuum conditions. We have investigated the coadsorption of CO and the room-temperature IL [CCIm][OTf] (1-ethyl-3-methylimidazolium trifluoromethanesulfonate) on Pd(111) by time-resolved infrared reflection-absorption spectroscopy, temperature-programmed reflection absorption spectroscopy, and temperature-programmed desorption. We find that the [OTf] anion adsorbs specifically to the Pd(111) surface via the SO group, thereby adopting a well-defined orientation with the molecular axis oriented perpendicular to the surface. At higher IL coverage, unspecific but oriented adsorption occurs, before the orientation is successively lost in the multilayer region. Upon coadsorption of [CCIm][OTf] on a CO-saturated Pd(111) surface at 300 K (θ = 0.5) a well-defined coadsorption layer is formed without any loss of adsorbed CO and with very similar CO site occupation. In the coadsorption layer [OTf] is specifically adsorbed between the CO with a molecular orientation perpendicular to the surface. Thus, a dense and homogeneous coadsorption layer is formed in which Pd surface atoms are simultaneously coordinated to both CO and [OTf] ions. From this compressed layer, CO desorbs with peak temperature at 410 K (heating rate, 3.3 K/s). Above this temperature, a low-coverage coadsorption phase of CO and surface-adsorbed IL resides, with little influence of the IL on the CO desorption temperature (peak temperature, 470 K). Coadsorption of the IL gives rise to a pronounced red shift of the CO stretching frequency in the order of 50 cm. The effect originates from the electrostatic interfacial field (Stark effect) generated by the coadsorbed IL and, at high coverage, possibly from additional short-range interactions. The results show that ILs form dense and well-defined mixed phases with strongly adsorbing reactants such as CO, in which a specifically adsorbed carpet of IL anions directly modifies the active surface sites by ligand-like effects.

Low-Temperature Synthesis of Oxides in Ionic Liquids: Ozone-Mediated Formation of Co3O4 Nanoparticles Monitored by In Situ Infrared Spectroscopy - Bauer, Tanja; Agel, Friederike; Blaumeiser, Dominik; Maisel, Sven; Görling, Andreas; Wasserscheid, Peter; Libuda, Jörg (Advanced Materials Interfaces, 2019)
For most functional oxides, structure-selective synthesis is the key for the task-specific production of nanomaterials. Herein, the low-temperature synthesis in ionic liquids (ILs) is an attractive strategy to produce nanomaterials which are not accessible otherwise is described. In this study, a bench-scale synthesis route toward Co3O4 by applying O3 on the molecular precursor Co2(CO)8 in IL medium is reported. The Co3O4 nanoparticles (NPs) are characterized by infrared (IR) spectroscopy, X-ray diffraction (XRD), and transmission electron microscopy (TEM). This protocol yields Co3O4 with good crystallinity and narrow size distribution. In addition to conventional materials characterization, a new experimental approach is described in which the material synthesis in situ by IR reflection absorption spectroscopy (IRAS) (in situ IRAS) is followed. The in situ approach provides additional information on the growth mechanisms and kinetics and confirms that O3 treatment of Co2(CO)8 in IL exclusively yields pure Co3O4 without the formation of byproducts or intermediates.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Co; cobalt oxide; ionic liquids; IR spectroscopy; ozone

Mechanistic Study of Ethanol Decomposition on Co3O4(111) and Pd/Co3O4(111) Model Catalysts - Reindl, Simone; Škvára, Jan; Hauner, Jonas; Simanenko, Alexander; Kastenmeier, Maximilian; Ronovský, Michal; Skála, Tomáš; Tsud, Nataliya; Kettner, Miroslav; Mehl, Sascha; Vorochta, Michael; Šmíd, Břetislav; et al. (ChemCatChem, 2024)
In many advanced catalytic materials, different functionalities are coupled through spillover of active species across heterogeneous interfaces. In the present work, we consider the coupling of a C─C bond cleavage functionality of palladium with the self-cleaning functionality of reducible Co3O4. On the model catalyst Pd/Co3O4(111)/Ir(100), we probed the interplay of the two functionalities for the selective decomposition of ethanol. In a systematic study, we compared the decomposition mechanisms of ethanol on Co3O4(111)/Ir(100) and Pd/Co3O4(111)/Ir(100) model catalysts using a variety of analytical techniques including synchrotron radiation photoelectron spectroscopy (SRPES), resonant photoemission spectroscopy (RPES), temperature programmed desorption (TPD), and near ambient pressure X-ray photoelectron spectroscopy (NAP-XPS). We found that ethanol decomposes via an ethoxy intermediate yielding acetaldehyde on Co3O4(111)/Ir(100). Remarkably, the spillover of ethanol/ethoxy species on Pd/Co3O4(111)/Ir(100) results in the selective formation of methane, hydrogen, and CO. Additionally, we observed CO2 resulting from the oxidative removal of carbonaceous deposits on Pd nanoparticles via spillover of active oxygen species released by Co3O4(111)/Ir(100) at higher temperatures. The onset of product formation and the product spectrum on both Co3O4(111)/Ir(100) and Pd/Co3O4(111)/Ir(100) depend strongly on the oxidation state of Co3O4. Complete removal of lattice oxygen from Co3O4(111) results in the deposition of large amounts of carbon.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Cobalt oxide; Ethanol; Nanoparticles; Palladium; Spillover

Metal-Support Interaction and Charge Distribution in Ceria-Supported Au Particles Exposed to CO - Bezkrovnyi, Oleksii; Bruix, Albert; Blaumeiser, Dominik; Piliai, Lesia; Schötz, Simon; Bauer, Tanja; Khalakhan, Ivan; Skala, Tomas; Matvija, Peter; Kraszkiewicz, Piotr; Pawlyta, Miroslawa; Vorokhta, Mykhailo; et al. (Chemistry of Materials, 2022)
Understanding how reaction conditions affect metal-support interactions in catalytic materials is one of the most challenging tasks in heterogeneous catalysis research. Metal nanoparticles and their supports often undergo changes in structure and oxidation state when exposed to reactants, hindering a straightforward understanding of the structure-activity relations using only ex situ or ultrahigh vacuum techniques. Overcoming these limitations, we explored the metal-support interaction between gold nanoparticles and ceria supports in ultrahigh vacuum and after exposure to CO. A combination of in situ methods (on powder and model Au/CeO2 samples) and theoretical calculations was applied to investigate the gold/ceria interface and its reactivity toward CO exposure. X-ray photoelectron spectroscopy measurements rationalized by first-principles calculations reveal a distinctly inhomogeneous charge distribution, with Au+ atoms in contact with the ceria substrate and neutral Au0 atoms at the surface of the Au nanoparticles. Exposure to CO partially reduces the ceria substrate, leading to electron transfer to the supported Au nanoparticles. Transferred electrons can delocalize among the neutral Au atoms of the particle or contribute to forming inert Au- atoms near oxygen vacancies at the ceria surface. This charge redistribution is consistent with the evolution of the vibrational frequencies of CO adsorbed on Au particles obtained using diffuse reflectance infrared Fourier transform spectroscopy.
CRIS-Team Scopus Importer:2022-09-16

Model Studies on the Ozone-Mediated Synthesis of Cobalt Oxide Nanoparticles from Dicobalt Octacarbonyl in Ionic Liquids - Schuster, Ralf; Wähler, Tobias; Kettner, Miroslav; Agel, Friederike; Bauer, Tanja; Wasserscheid, Peter; Libuda, Jörg (ChemistryOpen, 2020)
Low-temperature synthesis in ionic liquids (ILs) offers an efficient route for the preparation of metal oxide nanomaterials with tailor-made properties in a water-free environment. In this work, we investigated the role of 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide [C4C1Pyr][NTf2] in the synthesis of cobalt oxide nanoparticles from the molecular precursor Co2(CO)8 with ozone. We performed a model study in ultra-clean, ultrahigh vacuum (UHV) conditions by infrared reflection absorption spectroscopy (IRAS) using Au(111) as a substrate. Exposure of the pure precursor to ozone at low temperatures results in the oxidation of the first layers, leading to the formation of a disordered CoxOy passivation layer. Similar protection to ozone is also achieved by deposition of an IL layer onto a precursor film prior to ozone exposure. With increasing temperature, the IL gets permeable for ozone and a cobalt oxide film forms at the IL/precursor interface. We show that the interaction with the IL mediates the oxidation and leads to a more densely packed CoxOy film compared to a direct oxidation of the precursor.
CRIS-Team Scopus Importer:2020-09-25
Keywords: cobalt oxide; ionic liquids; IR spectroscopy; low temperature synthesis; ozone

Molecular and Structural Insights into H2 Indicator Supraparticles: Lowering the Limit of Detection by Tuning Incorporated Catalyst Nanoparticles - Zhang, Kailun; Reichstein, Jakob; Groppe, Philipp; Schötz, Simon; Stockinger, Nina; Libuda, Jörg; Mandel, Karl; Wintzheimer, Susanne; Retzer, Tanja (Chemistry of Materials, 2023)
With the increasing interest in H2-based energy storage, H2 detectors gain significant importance. Here, we report on safe, i.e., spark-free, reliable, and highly reactive gasochromic H2 indicator supraparticles (SPs). They are assembled from different types of noble metal nanoparticles (NPs), SiO2 NPs, and the dye resazurin via spray-drying. Their sensing principle is based on the adsorption and activation of H2 on catalytically active noble metal NPs incorporated in the mesoporous supraparticulate framework. Upon stepwise hydrogenation of resazurin molecules with molecular mobility via activated H species, the indicator displays a fast color change visible to the naked eye. We investigate the effect of incorporating different catalytically active NPs into indicator SPs on their sensor performance at different H2 concentrations. We find that the size and material of the catalyst NPs have a strong influence on the sensor response of the H2 indicator as it changes the amount of activated H species available in the system. Enhancing the amount of interstitial H2O in the mesopores of the SPs increases their reaction volume but impairs the reproducibility of their sensor response. Among the studied materials, dispersed Pt NP-containing SPs give the overall best results in terms of overall performance toward H2 detection.<br

NAP-XPS and in Situ DRIFTS of the Interaction of CO with Au Nanoparticles Supported by Ce1- xEuxO2 Nanocubes - Bezkrovnyi, O. S.; Blaumeiser, Dominik; Vorokhta, M.; Kraszkiewicz, P.; Pawlyta, M.; Bauer, Tanja; Libuda, Jörg; Kepinski, L. (Journal of Physical Chemistry C, 2020)
Control of metal-support interactions is one of the major challenges in heterogeneous catalysis. In this study, we explored the effect of Eu doping on the metal-support interactions in Au/Ce1-xEuxO2 catalysts applied in the oxidation of CO. We probe the catalysts with CO under realistic conditions by near-ambient-pressure X-ray photoelectron spectroscopy (NAP-XPS) and in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). NAP-XPS allows in situ investigation of the surface reducibility of the ceria support and charging of the Au nanoparticles. Both parameters are crucial, as they are responsible for the efficiency of Au/ceria catalysts in the CO oxidation. We found that doping of the ceria support with Eu decreases the reducibility of Ce4+ in the Au/Ce1-xEuxO2 system and the population of Auδ+ sites. We identified the available CO adsorption sites on Au/ceria (Auδ-, Au0, and Auδ+) in the typical temperature window of the CO oxidation reaction by in situ DRIFTS. We found that the difference in the catalytic activity of Au/CeO2 and Au/Ce0.80Eu0.20O2 does not origin from an electronic effect of the Eu dopant or different adsorption sites but from the size of the Au nanoparticles. The most active Au nanoparticles are very small, reactive Au nanoparticles, which are exclusively present on the undoped ceria support.
CRIS-Team Scopus Importer:2020-04-03

Operando DRIFTS and DFT Study of Propane Dehydrogenation over Solid- and Liquid-Supported GaxPty Catalysts - Bauer, Tanja; Maisel, Sven; Blaumeiser, Dominik; Vecchietti, Julia; Taccardi, Nicola; Wasserscheid, Peter; Bonivardi, Adrian; Görling, Andreas; Libuda, Jörg (ACS Catalysis, 2019)
Supported catalytically active liquid metal solutions (SCALMS) represent a class of catalytic materials that have only recently been developed, but have already proven to be highly active, e.g., for dehydrogenation reactions. Previous studies attributed the catalytic activity to isolated noble metal atoms at the surface of a liquid and inert Ga matrix. In this study, we apply diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) with CO as a probe molecule to Ga/Al2O3, Pt/Al2O3, and Ga37Pt/Al2O3 catalysts, to investigate in detail the nature of the active Pt species. Comparison of CO adsorption on Pt/Al2O3 and Ga37Pt/Al2O3 shows that isolated Pt atoms are, indeed, present at the surface of the liquid SCALMS. Combining DRIFTS with online gas chromatography (GC), we investigated the Ga/Al2O3, Pt/Al2O3, and Ga37Pt/Al2O3 systems under operando conditions during propane dehydrogenation in CO/propane and in Ar/propane. We find that the Pt/Al2O3 sample is rapidly poisoned by CO adsorption and coke, whereas propane dehydrogenation over Ga37Pt/Al2O3 SCALMS leads to higher conversion with no indication of poisoning effects. We show under operando conditions that isolated Pt atoms are present at the surface of SCALMS during the dehydrogenation reaction. IR spectra and density-functional theory (DFT) suggest that both the Ga matrix and the presence of coadsorbates alter the electronic properties of the surface Pt species.
CRIS-Team WoS Importer:2019-04-23

Palladium-Mediated Ethylation of the Imidazolium Cation Monitored In Operando on a Solid Catalyst with Ionic Liquid Layer - Bauer, Tanja; Hager, Veit; Williams, Marc; Laurin, Mathias; Döpper, Tibor; Görling, Andreas; Szesni, Normen; Wasserscheid, Peter; Haumann, Marco; Libuda, Jörg (ChemCatChem, 2017)
The ionic liquid 1-ethyl-3-methylimidazolium ethylsulfate [EMIM][EtOSO] was supported on Pd-AlO to yield a solid catalyst with ionic liquid layer (SCILL) material. During the hydrogenation of ethene, it was found that ethene was incorporated into the imidazolium moiety in a reaction catalyzed by the palladium surface. The formation of 1,2-diethyl-3-methylimidazolium ethylsulfate was confirmed ex situ by means of NMR spectroscopy. Moreover, the reaction itself could be monitored in situ by diffuse reflection infrared Fourier transformation (DRIFT) spectroscopy. A reaction mechanism involving surface carbene species was proposed on the basis of the analytical data.
Keywords: carbenes; heterogeneous catalysis; ionic liquids; palladium; reaction mechanisms

Pd nanoparticle formation in ionic liquid thin films monitored by in situ vibrational spectroscopy - Mehl, Sascha; Toghan, Arafat; Bauer, Tanja; Brummel, Olaf; Taccardi, Nicola; Wasserscheid, Peter; Libuda, Jörg (Langmuir, 2015)
Ionic liquids (ILs) are flexible reaction media and solvents for the synthesis of metal nanoparticles (NPs). Here, we describe a new preparation method for metallic NPs in nanometer thick films of ultraclean ILs in an ultrahigh vacuum (UHV) environment. CO-covered Pd NPs are formed by simultaneous and by sequential physical vapor deposition (PVD) of the IL and the metal in the presence of low partial pressures of CO. The film thickness and the particle size can be controlled by the deposition parameters. We followed the formation of the NPs and their thermal behavior by time-resolved IR reflection absorption spectroscopy (TP-IRAS) and by temperature-programmed IRAS (TR-IRAS). Codeposition of Pd and [CCIm][OTf] in CO at 100 K leads to the growth of homogeneous multilayer films of CO-covered Pd aggregates in an IL matrix. The size of these NPs can be controlled by the metal fraction in the co-deposit. With increasing metal fraction, the size of the Pd NPs also increases. At very low metal content, small Pd carbonyl-like species are formed, which bind CO in on-top geometry only. Upon annealing, the [OTf] anion coadsorbs at the NP surface and partially displaces CO. Co-adsorption of CO and IL is indicated by a strong red-shift of the CO stretching bands. While the weakly bound on-top CO is mainly replaced below the melting transition of the IL, coadsorbate shells with bridge-bonded CO and IL are stable well above the melting point. Larger three-dimensional Pd NPs can be prepared by PVD of Pd onto a solid [CCIm][OTf] film at 100 K. Upon annealing, on-top CO desorbs from these NPs below 200 K. Upon melting of the IL film, the CO-covered Pd NPs immerse into the IL and again form a stable coadsorbate shell that consists of bridge-bonded CO and the IL.

Site blocking effects on P-modified Pd/Al2O3 catalysts for LOHC hydrogenation: an in situ DRIFTS study - Sheng, Yaoci; Seitz, Adrian; Gambu, Thobani; Zhang, Kailun; Schühle, Patrick; Retzer, Tanja (Catalysis: Science and Technology, 2025)
In this paper, we investigate structural changes of a P-modified Pd/Al2O3 catalyst for the hydrogenation of liquid organic hydrogen carriers (LOHCs) e.g., benzyltoluene (H0-BT). We elucidate the effect of P modification on the Pd nanoparticles (NPs) and the support material via a systematic combination of reactor studies, in situ diffuse reflectance FT-IR spectroscopy using CO as a probe molecule (CO-DRIFTS), and density functional theory (DFT). We find that P modification induces structural changes as well as site-blocking effects on the Pd NPs. In particular, phosphates on the Al2O3 support induce the formation of smaller Pd NPs. Phosphate species further reside on the terrace sites of Pd NPs, which leads to competitive adsorption between phosphates and CO/H2 especially at the Pd(111) facet. This demonstrates rearrangement of surface and adsorbate species on the P-modified Pd/Al2O3 catalysts under reactive gas atmosphere.
CRIS-Team Scopus Importer:2025-05-09

Supraparticles for Bare-Eye H2 Indication and Monitoring: Design, Working Principle, and Molecular Mobility - Reichstein, Jakob; Schötz, Simon; Macht, Moritz; Maisel, Sven; Stockinger, Nina; Cuadrado Collados, Carlos; Schubert, Katrin; Blaumeiser, Dominik; Wintzheimer, Susanne; Görling, Andreas; Thommes, Matthias; Zahn, Dirk; et al. (Advanced Functional Materials, 2022)
Indicators for H2 are crucial to ensure safety standards in a green hydrogen economy. Herein, the authors report micron-scaled indicator supraparticles for real-time monitoring and irreversible recording of H2 gas via a rapid eye-readable two-step color change. They are produced via spray-drying SiO2 nanoparticles, AuPd nanoparticles, and indicator-dye resazurin. The resulting gas-accessible mesoporous supraparticle framework absorbs water from humid atmospheres to create a three-phase-system. In the presence of H2, the color of the supraparticle switches first irreversibly from purple to pink and further reversibly to a colorless state. In situ infrared spectroscopy measurements indicate that this color change originates from the (ir)reversible H2-induced reduction of resazurin to resorufin and hydroresorufin. Further infrared spectroscopic measurements and molecular dynamics simulations elucidate that key to achieve this functionality is an established three-phase-system within the supraparticles, granting molecular mobility of resazurin. Water acts as transport medium to carry resazurin molecules towards the catalytically active AuPd nanoparticles. The advantages of the supraparticles are their small dimensions, affordable and scalable production, fast response times, straightforward bare-eye detection, and the possibility of simultaneously monitoring H2 exposure in real-time and ex post. Therefore, H2 indicator supraparticles are an attractive safety additive for leakage detection and localization in a H2 economy.<br
Keywords: hydrogen indicators; hydrogen sensors; in situ DRIFTS measurements; MD simulations; smart additives; supraparticles

Supraparticles for naked‑eye H2 indication and monitoring: improving performance by variation of the catalyst nanoparticles - Zhang, Kailun; Schötz, Simon; Reichstein, Jakob; Groppe, Philipp; Stockinger, Nina; Wintzheimer, Susanne; Mandel, Karl; Libuda, Jörg; Retzer, Tanja (Journal of Chemical Physics, 2023)
The recent transition to H2-based energy storage demands reliable H2 sensors that allow for easy, fast, and reliable detection of leaks. Conventional H2 detectors are based on the changes of physical properties of H2 probes induced by subsurface H-atoms to a material such as electrical conductivity. Herein, we report on highly reactive gasochromic H2 detectors based on the adsorption of H2 on the material surface. We prepared supraparticles (SPs) containing different types of noble metal nanoparticles (NPs), silica NPs, and the dye resazurin by spray-drying and tested their performance for H2 detection. The material undergoes a distinct color change due to the hydrogenation of the purple resazurin to pink resorufin and, finally, colorless hydroresorufin. The stepwise transition is fast and visible to the naked eye. To further improve the performance of the sensor, we tested the reactivity of SPs with different catalytically active NPs by means of in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). We show that the choice of the NP catalyst has a pronounced effect on the response of the H2 indicator. In addition, we demonstrate that the performance depends on the size of the NPs. These effects are attributed to the availability of reactive H-atoms on the NP surface. Among the materials studied, Pt-containing SPs gave the best results for H2 detection.

Thermal Stability and CO Permeability of [C4C1Pyr][NTf2]/Pd(111) Model SCILLs: from UHV to Ambient Pressure - Eschenbacher, Roman; Trzeciak, Simon; Schuschke, Christian; Schötz, Simon; Hohner, Chantal; Blaumeiser, Dominik; Zahn, Dirk; Retzer, Tanja; Libuda, Jörg (Topics in Catalysis, 2023)
Solid catalysts with ionic liquid layers (SCILLs) are heterogeneous catalysts which benefit significantly in terms of selectivity from a thin coating of an ionic liquid (IL). In the present work, we study the interaction of CO with a Pd model SCILL consisting of a 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)-imide ([C4C1Pyr][NTf2]) film deposited on Pd(111). We investigate the CO permeability and stability of the IL film via pressure modulation experiments by infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV) and at ambient pressure conditions by time-resolved, temperature-programmed, and polarization-modulated (PM) IRAS experiments. In addition, we performed molecular dynamics (MD) simulations to identify adsorption motifs, their abundance, and the influence of CO. We find a strongly bound IL wetting monolayer (ML) and a potentially dewetting multilayer. Molecular reorientation of the IL at the interface and multilayer dewetting allow for the accumulation of CO at the metal/IL interface. Our results confirm that co-adsorption of CO changes the molecular structure of the IL wetting layer which confirms the importance to study model SCILL systems under in situ conditions. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-04-14
Keywords: In Situ; Infrared Spectroscopy; Ionic Liquids; Molecular Dynamics; Permeability; SCILL

Wilkinson-type catalysts in ionic liquids for hydrogenation of small alkenes: understanding and improving catalyst stability - Kratzer, Eva; Schötz, Simon; Maisel, Sven; Blaumeiser, Dominik; Khan Antara, Sharmin; Ewald, Leon; Dotzel, Daniel; Haumann, Marco; Görling, Andreas; Korth, Wolfgang; Jess, Andreas; Retzer, Tanja (Catalysis: Science and Technology, 2023)
In this work, we apply supported ionic liquid phase (SILP) catalysts to hydrogenate 1-alkenes in a continuous fixed-bed reactor. SILP catalyts were prepared using the ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [C4C1Im][NTf2] and tris(triphenylphosphine)rhodium(i) chloride [RhCl(PPh3)3] as a dissolved catalyst. Under isothermal conditions, we observe an increase in activity related to restructuring of the catalyst via formation of supported metal nanoparticles (NPs). Combined in situ infrared spectroscopic and theoretical studies show that NP formation is a step-wise process including the sequential loss of ligands and formation of isolated, supported Rh+-ions as intermediates. To stabilize the highly selective homogeneous catalyst, we systematically vary the experimental conditions (co-feeding of CO) and catalyst design (application of strongly binding CO or chelating xantphos ligand). This knowledge-driven approach results in a stabilization of the molecular Rh complex under hydrogenation conditions.
CRIS-Team Scopus Importer:2023-03-24

ZnO Nanoparticle Formation from the Molecular Precursor [MeZnOtBu](4) by Ozone Treatment in Ionic Liquids: in-situ Vibrational Spectroscopy in an Ultrahigh Vacuum Environment - Bauer, Tanja; Voggenreiter, Markus; Xu, Tao; Wähler, Tobias; Agel, Friederike; Pohako-Esko, Kaija; Schulz, Peter; Döpper, Tibor; Görling, Andreas; Polarz, Sebastian; Wasserscheid, Peter; Libuda, Jörg (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
As reported previously, novel ZnO nanostructures can be grown by oxidation of [MeZnOtBu](4) building blocks with O-3 in ionic liquids (ILs). In this study, we have explored the role of the IL during ZnO formation by in-situ infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV). [MeZnOtBu](4) and [C(2)C(1)Im][OTf] were (co-)deposited as thin films by physical vapor deposition (PVD) onto Au(111), separately or simultaneously. The IR spectrum of [MeZnOtBu](4) was analyzed between 300 and 4000 cm(-1) based on calculated spectra from density-functional theory (DFT). Spectral changes in the IL-related bands during the thermal treatment of [MeZnOtBu](4) in [C(2)C(1)Im][OTf] indicate the loss of the precursor ligands and the interaction of the IL with the growing ZnO aggregates. The films were treated with ozone (10(-6) mbar) in UHV and the spectral changes were monitored in-situ by IRAS. Slow ozonolysis of [C(2)C(1)Im][OTf] is observed. Spectroscopically we identify the primary ozonide formed by addition of O-3 to [C(2)C(1)Im](+) and suggest a reaction mechanism, which leads to a biuret derivative. Upon ozone treatment of mixed [MeZnOtBu](4)/[C(2)C(1)Im][OTf] films, ZnO aggregates are formed at the IL/vacuum interface. Ozonolysis of [C(2)C(1)Im][OTf] is suppressed. Upon annealing to 320 K, further ZnO aggregates are formed, leading to enclosure of [C(2)C(1)Im][OTf] in the ZnO film. At 380 K the IL is released from the mixed film. The pure [C(2)C(1)Im][OTf] desorbs at 420 K, leaving behind the ZnO phase.
Keywords: Ionic liquid; Ozone; IR spectroscopy; ZnO nanoparticles; Surface science

ZnO Nanoparticle Formation from the Molecular Precursor [MeZnOtBu]4 by Ozone Treatment in Ionic Liquids: in-situ Vibrational Spectroscopy in an Ultrahigh Vacuum Environment - Bauer, Tanja; Voggenreiter, Markus; Xu, Tao; Wähler, Tobias; Agel, Friederike; Pohako-Esko, Kaija; Schulz, Peter; Döpper, Tibor; Görling, Andreas; Polarz, Sebastian; Wasserscheid, Peter; Libuda, Jörg (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
As reported previously, novel ZnO nanostructures can be grown by oxidation of [MeZnOtBu]“building blocks” with Oin ionic liquids (ILs). In this study, we have explored the role of the IL during ZnO formation by in-situ infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV). [MeZnOtBu]and [CCIm][OTf] were (co-)deposited as thin films by physical vapor deposition (PVD) onto Au(111), separately or simultaneously. The IR spectrum of [MeZnOtBu]was analyzed between 300 and 4000 cmbased on calculated spectra from density-functional theory (DFT). Spectral changes in the IL-related bands during the thermal treatment of [MeZnOtBu]in [CCIm][OTf] indicate the loss of the precursor ligands and the interaction of the IL with the growing ZnO aggregates. The films were treated with ozone (10mbar) in UHV and the spectral changes were monitored in-situ by IRAS. Slow ozonolysis of [CCIm][OTf] is observed. Spectroscopically we identify the primary ozonide formed by addition of Oto [CCIm]and suggest a reaction mechanism, which leads to a biuret derivative. Upon ozone treatment of mixed [MeZnOtBu]/[CCIm][OTf] films, ZnO aggregates are formed at the IL/vacuum interface. Ozonolysis of [CCIm][OTf] is suppressed. Upon annealing to 320 K, further ZnO aggregates are formed, leading to enclosure of [CCIm][OTf] in the ZnO film. At 380 K the IL is released from the mixed film. The pure [CCIm][OTf] desorbs at 420 K, leaving behind the ZnO phase.
Keywords: Ionic liquid; Ozone; IR spectroscopy; ZnO nanoparticles; Surface science